(untitled) (Revista Apotheke, 2023)
This paper presents to carry out ananalysis of a brief corpus of the work of the Mexican artist, Mar Coyol. Through the problematization of categoriessuch as queer/cuir, sex, and genderdissident, wesoughtto do a critical and sensitiveapproachtoimages of twoworks: “Prietx mi cuerpx, mariconx mi barrio”(2023) and “Mariconx resiste”(2020). Forthis, the interpretation of these art Works was built through the discourse of the artista about the ir work, which was recove redthrough the application of a virtual interview, combinedwith a semioticapproachto the symbolicelementspresent in saidpaintings.